The Effect of Rainfall on Rice and Corn Crop Production in Sleman District - Marina Evana Putri Darise (International Journal Labs, 2023)
Rainwater that falls to the surface of the earth is very important for the growth of agricultural crops such as rice and corn. Therefore, this study aims to know rice and corn production in 2018 and 2020, determine rainfall in 2018 and 2020 and analyze the effect of rainfall on rice and corn production in 2018 and 2020 in Sleman District. The data used by this research is data from Sleman District in 2018 and 2020 Figures. The data were analyzed in a qualitative descriptive manner. The results of the study found that rice production in 2018 amounted to 1,574.3 tons, rose to 16,135 tons in 2020, while corn production in 2018 was 452.7 tons, rose to 5,763 tons in 2020. The total rainfall in Sleman District in 2018 was 2,526 mm with the maximum rainfall occurring in December at 178 mm, while the total rainfall in 2020 was 3,272 mm with maximum rainfall occurring in December with rainfall of 184 mm slightly lower than in 2018. The study also found that rainfall in 2018 and 2020 directly affected rice and jangun production.